Study Motivation: Review Of 58 Research Papers - Lambok P. Sagala (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2016)
The importance of study motivation has encouraged many stakeholders to conduct evaluation on many issues related to study motivaton. This research was done to see how far evaluation of study motivation has been implemented. The result of this research is expected to be a guideline for the further study. Fifty-eight research papers which were available online used as references. The research found that most of the researchers used likert scale measurement for data collection; data collection used sampling method; most of the researches location are located in West Java province, and students were the main object of the research. There are 3 researches related to study motivation done in Riau Province. This research also revealed that less study done in vocational schools level and the measurement mostly done uncompletely as they have not accommodated all aspects related to motivation (e.g. the research object only limited to students).